An exploratory study on the psychological meaning of ancestral calling by nanga dza Vhavenda - Sigida, Salome Thilivhali (My University, 2022)
The training to become a traditional healer has been under scrutiny because of the symptoms that are experienced during ancestral calling. Ancestral calling usually presents itself in the form of a mysterious physical or psychological illness that will not ordinarily respond to western treatment. The Eurocentric perspective interprets the symptoms of ancestral calling and the resultant process to become a traditional health practitioner as a manifestation of some psychological disturbance. The researcher embarked on a journey with traditional health practitioners to understand their lived experiences and explored the psychological meanings of Vhavenda ancestral calling with a view to identifying and documenting the psychological meanings embedded in this culturally entrenched practice. A qualitative research method located within the interpretative paradigm was used. A descriptive phenomenological research design was adopted to explore the lived experiences of traditional health practitioners who have gone through the process of ancestral calling. Both snowball and purposive sampling methods were used to recruit 17 participants until saturation was researched in the findings. The six major themes that emerged are: a) signs of ancestral calling; b) meaning attached to ancestral calling; c) help-seeking pathway following an ancestral call; d) responding to the ancestral call; e) roles of the master healer; and f) post training realities and experiences. The findings of the study revealed that there are several symptoms that are indicative that one has an ancestral calling. These symptoms are often misunderstood and misdiagnosed when interpreted from the Eurocentric perspective. However, accepting the ancestral calling and going through training is linked with identity formation. The findings also revealed that ancestral calling is a life-transforming and therapeutic experience and a journey of self realisation
Thesis (Ph.D. (Psychology)) -- University of Limpopo, 2022
Keywords: Ancestral calling; Vhavenda; Traditional health practitioner; Afrocentric; Ancestor worship; Ancestral shrines; Healers